Pelatihan Pembuatan Natural Bar Soap Berbasis Eco Enzyme Bersama Pkk Kecamatan Beruntung Baru, Kalimantan Selatan - Dr.Dian Masita Dewi, SE.,MM; Ikhwan Faisal; Anisa Yulia Al Munawaroh1; Ririn Kurniawati; Anton Yuda Sumanto (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2023)
This Community Service Program is a continuation program of the socialization and training program including the use of eco enzyme with the PKK Beruntung Baru District in 2021. The community has felt the benefits and has proven the benefits of eco enzyme for agriculture, health and even for a substitute for bath soap. However, eco enzyme has disadvantages for some people including not foaming and feeling sticky on the skin and some people do not like the aroma. Eco enzyme has social value so it is not allowed to be traded. Based on this background, the PKM team took the initiative to carry out a follow-up program, namely training in making natural bar soap based on eco enzyme which is competitive and has high economic value so that it can improve the economy and welfare of the Beruntung Baru sub-district community. The methods that will be used in this PKM activity are lectures, simulations or demonstrations and direct practice of making eco enzyme-based natural bar soap. Based on the results of the evaluation of the Eco Enzyme-based Natural Bar Soap Making Training activities carried out by the PDWA Year 2023 Team from the Lambung Mangkurat University Eco Enzyme Study Center, this is the right solution in overcoming partner problems and the results of the pre and post test evaluation of the entire PDWA Th 2023 program implemented by the ULM Eco Enzyme Study Center through the Eco Enzyme-Based Natural Bar Soap Making Training at PKK Kec. Beruntung Baru, Kab. Banjar, South Kalimantan Province can be categorized as very successful